Evaluación de aprendizajes para el fortalecimiento del pensamiento crítico (2019)
Learning demands new ways of reconstructing knowledge and modifying behaviors. In turn, this process requires the student to use cognitive structures to improve thinking as a result of a study of what is learned and that must be manifested both in the teaching and learning process and in the evaluation in the classroom. This research project aims to contribute to the improvement of the evaluation process, generating an instrument that strengthens the way of analyzing, understanding and organizing knowledge as evidence of learning and the strengthening of critical thinking. Authors such as Ianfrancesco (2005), Casanova (1998), Fernández (2009) among others are approached for evaluation; and Paul and Elder (2005), for critical thinking. It is developed from the interpretive paradigm with a projective approach and a series of techniques of the mixed method are implemented, such as observation and survey. The quantitative and qualitative analysis of the results found allows an interpretation of the conceptions that educators have about evaluation and critical thinking and their implications when evaluating their students. The result is projected in the creation of a proposal focused on the design of a learning assessment instrument for the strengthening of critical thinking, which is feasible because the elements it is made of are derived from the postulates of the authors of critical thinking and evaluation, validated by experts and they accredits it as an effective and efficient tool for the qualification of the evaluation process.